Association between clinical diagnosis of temporomandibular disorders using research diagnostic criteria and morphological changes of the condyle and abnormal joint spaces using CBCT - G A Prarthana; Sowmya Krishna; T A Deepak; Vinaya R Pawar; B K Ramnarayan; M Lokapriya (Wolters Kluwer Medknow Publications, 2023)
Background: Temporomandibular disorders (TMDs) include pathologies related to pain and abnormalities in the joints and muscles that control the mandibular movements. Objectives: The objective of the study was to evaluate the association between clinical diagnosis of subjects suffering from TMD as diagnosed with RDC/TMD with radiographic findings of condyle and joint spaces using CBCT. Methods: An analytical study was conducted on 70 subjects with signs, symptoms, and functional changes related to TMDs as assessed clinically by RDC/TMD. Radiographic changes of condyle such as erosion, flattening, sclerosis, and osteophyte were examined on CBCT. The Chi-square test assessed the association between clinical diagnosis and morphological changes and also clinical diagnosis and joint space findings through CBCT among study subjects. The P value was kept as < 0.005. Results: Among 70 subjects, clinical diagnosis was associated with multiple morphological changes and abnormal joint spaces in most of the study subjects. Conclusion: In our study, the peak age of TMD prevalence was 20-40 years with female predilection. Even though there were multiple radiographic findings for a single clinical diagnosis of TMD, the study showed a statistically significant association between clinical diagnosis and radiographic findings.